Radio Talk Show: Seni Minimalis Kelola Keuangan Tipis - Alpiansah, Restu; Pratama, Aryan Agus; Yuliana, Ika; Ramdani, Rizal; Dewi, Puspita (Insan Kreasi Media, 2023)
In the modern era, when e-commerce such as Shopee, Tokopedia and other platforms dominate the business market, the young generation (Millennial Generation) takes a particular role. When they have money or gain a salary, they do not know how to manage it. They buy impulse and buy anything they want, not what they need. Based on this, financial literacy must be informed and explained to the young generation so that they can understand the importance of money management in life. Being minimalist by minimum budget is introduced in this talk show to spread the minimalist financial vibes to the millennial generation. This article aims to share knowledge about managing money using the minimalist concept, which has been transferred and broadcasted on Radio using sharing session method. Finally, Millennial generations close to technology should be able to control their financial budget to have good financial health. More investment in many sectors is suggested to have an excellent financial condition in the future. A good financial situation is started with how to manage the financial budget.